IL-6 augments IL-4-induced polarization of primary human macrophages through synergy of STAT3, STAT6 and BATF transcription factors. (3rd October 2018) - Gupta, Sahil; Jain, Arpit; Syed, Shahzad Nawaz; Snodgrass, Ryan G.; Pflüger-Müller, Beatrice; Leisegang, Matthias S.; Weigert, Andreas; Brandes, Ralf P.; Ebersberger, Ingo; Brüne, Bernhard; Namgaladze, Dmitry
ABSTRACT: Macrophages in the tumor microenvironment respond to complex cytokine signals. How these responses shape the phenotype of tumor-associated macrophages (TAMs) is incompletely understood. Here we explored how cytokines of the tumor milieu, interleukin (IL)-6 and IL-4, interact to influence target gene expression in primary human monocyte-derived macrophages (hMDMs). We show that dual stimulation with IL-4 and IL-6 synergistically modified gene expression. Among the synergistically induced genes are several targets with known pro-tumorigenic properties, such as CC-chemokine ligand 18 (CCL18), transforming growth factor alpha (TGFA) or CD274 (programmed cell death 1 ligand 1 (PD-L1)). We found that transcription factors of the signal transducer and activator of transcription (STAT) family, STAT3 and STAT6 bind regulatory regions of synergistically induced genes in close vicinity. STAT3 and STAT6 co-binding further induces the basic leucine zipper ATF-like transcription factor (BATF), which participates in synergistic induction of target gene expression. Functional analyses revealed increased MCF-7 and MDA-MB 231 tumor cell motility in response to conditioned media from co-treated hMDMs compared to cells incubated with media from single cytokine-treated hMDMs. Flow cytometric analysis of T cell populations upon co-culture with hMDMs polarized by different cytokines indicated that dual stimulation promoted immunosuppressive properties of hMDMs in a PD-L1-dependent manner. Analysis of clinical data revealed increased expression of BATF together with TAM markers in tumor stroma of breast cancer patients as compared to normal breast tissue stroma. Collectively, our findings suggest that IL-4 and IL-6 cooperate to alter the human macrophage transcriptome, endowing hMDMs with pro-tumorigenic properties.